Defects of mtDNA replication impaired mitochondrial biogenesis during Trypanosoma cruzi infection in human cardiomyocytes and Chagasic patients: The role of Nrf1/2 and antioxidant response - Wan, Xianxiu (2012)
Mitochondrial dysfunction is a key determinant in chagasic cardiomyopathy development in mice; however, its relevance in human Chagas disease is not known. We determined if defects in mitochondrial biogenesis and dysregulation of peroxisome proliferator-activated receptor gamma (PPARγ) coactivator-1 (PGC-1)-regulated transcriptional pathways constitute a mechanism or mechanisms underlying mitochondrial oxidative-phosphorylation (OXPHOS) deficiency in human Chagas disease. We utilized human cardiomyocytes and left-ventricular tissue from chagasic and other cardiomyopathy patients and healthy donors (n>6/group). We noted no change in citrate synthase activity, yet mRNA and/or protein levels of subunits of the respiratory complexes were significantly decreased in Trypanosoma cruzi-infected cardiomyocytes (0 to 24 hours) and chagasic hearts. We observed increased mRNA and decreased nuclear localization of PGC-1-coactivated transcription factors, yet the expression of genes for PPARγ-regulated fatty acid oxidation and nuclear respiratory factor (NRF1/2)-regulated mtDNA replication and transcription machinery was enhanced in infected cardiomyocytes and chagasic hearts. The D-loop formation was normal or higher, but mtDNA replication and mtDNA content were decreased by 83% and 40% to 65%, respectively. Subsequently, we noted that reactive oxygen species (ROS), oxidative stress, and mtDNA oxidation were significantly increased, yet NRF1/2-regulated antioxidant gene expression remained compromised in infected cardiomyocytes and chagasic hearts. The replication of mtDNA was severely compromised, resulting in a significant loss of mtDNA and expression of OXPHOS genes in T cruzi-infected cardiomyocytes and chagasic hearts. Our data suggest increased ROS generation and selective functional incapacity of NRF2-mediated antioxidant gene expression played a role in the defects in mtDNA replication and unfitness of mtDNA for replication and gene expression in Chagas disease.